Psyche as the Principle and Cause of Life in Aristotle - Meyer, Martin F. (Peitho. Examina Antiqua, 2012)
Biology is the most extensive field in the Corpus Aristotelicum. In his fundamental work De anima, Aristotle tries to fix the borders of this life science. The term ψυχή has a twofold explanatory status. On the one hand, ψυχή is understood as a principle of all living beings. On the other hand, it is understood as a cause of the fact that all living beings are alive. The paper is divided into three sections. (1) The first part shows why Aristotle discusses these issues in a work entitled Περὶ ψυχῆς. Since Pythagoras and Heraclitus, ψυχή was understood as a life principle: Pythagoras believed that men, animals and plants share the same nature: they are all ἔμψυχα and they are homogenous qua ψυχή. (2) The second part of this article deals with Aristotle’s definition of the soul in DA II: ψυχή is the principle of all living things. This establishes (i) the external criteria to divide living and non-living beings and (ii) the internal criteria to divide living beings. (3) The third part of this paper is concerned with the methodological consequences of this definition: the life functions (δυνάμεις τῆς ψυχῆς) are the central explanandum in Aristotle’s biology. De anima II defines such various life-functions as nourishment, sense-perception and locomotion. These capacities contour the main fields of the philosopher’s biological investigation. For Aristotle, the faculty of reproduction is a subtype of nourishment. Reproduction is the most important and most natural function of all living beings. Genetics is, therefore, the most important field in Aristotle’s biology.